The Routledge companion to postcolonial African historiography
1 online resource
Keywords: "The Routledge Companion to Postcolonial African Historiography explores history's fortunes in Modern Africa south of the Sahara, from the discipline's Golden Age as a handmaiden in struggles against colonialism, to difficult decades when its survival has been threatened by capricious political and economic conditions, and the uncertain present where the continent's historians struggle to justify their value to frequently sceptical publics. In exploring the discipline's practical role in past struggles for African emancipation the volume speaks directly to these challenging but changing circumstances. The chapters feature contributions from leading experts on historiographical traditions of different regions of the continent. They collectively demonstrate how the process of instrumentalizing the past to advance lay struggles has influenced the choices historians have made regarding sources, methodology, interpretation, audiences, and platforms. This practical application has strongly shaped the diverse forms that African historiography has assumed, as reflected in this book. The themes discussed offer a platform for inserting Africa into comparative studies of global historiographical traditions, whilst also contributing to contemporary debates on decolonisation. In offering accessible insights from leading historians, this is an essential handbook for students and scholars of African history and historiography, as well as all those interested in postcolonial studies"-- Provided by publisher.